Prognostic alternative mRNA splicing in lung adenocarcinoma - Su, Panke; Xu, Pei; Xu, Deying (Frontiers in Oncology, 2025)
BackgroundAlternative splicing (AS) of mRNA has emerged as a promising biomarker for various tumors, playing a crucial role throughout nearly all stages of tumor progression and influencing the tumor immune microenvironment (TIME). Our study was designed to develop an AS-based signature for accurate prognosis prediction in lung adenocarcinoma (LUAD) patients, to delineate the associated immune cell landscape, and to pinpoint promising drug targets.MethodsPrognostic alternative splicing events (PASEs) were identified through univariate Cox regression analysis of RNA-Seq data from The Cancer Genome Atlas (TCGA). These PASEs were incorporated into a least absolute shrinkage and selection operator–Cox proportional hazards model to develop a prognostic signature. Experimental validation was performed using reverse transcription quantitative polymerase chain reaction, immunohistochemistry, and functional assays in vitro and in vivo.ResultsA total of 13 PASEs were selected to form the prognostic signature, which demonstrated excellent predictive power for 1-, 2-, and 3-year overall survival (OS), with area under the receiver operating characteristic curve values of 0.776, 0.751, and 0.767, respectively. High-risk patients, identified by the signature, showed significantly decreased stromal, immune, and combined scores; increased tumor purity (P< 0.001); a reduced prevalence of various immune cell types; diminished immune cell activity; and decreased expression of immune checkpoint genes. Notably, elevated expression of cyclin-dependent kinase inhibitor 2A (CDKN2A), a gene associated with PASEs, correlated with poorer OS and significantly higher infiltration of CD8+ T cells, activated memory CD4+ T cells, and M1 macrophages compared to patients with lower expression. Further validation studies confirmed increased CDKN2A levels in LUAD tissues, with CDKN2A protein expression inversely correlated with LUAD prognosis (hazard ratio = 2.737; 95% confidence interval, 1.524–4.915; P = 0.0002). CDKN2A was found to promote LUAD progression in vitro. Molecular docking identified YM-201636 and VE-822 (Berzosertib) as potential drugs targeting CDKN2A, both showing promise for LUAD treatment in vivo.ConclusionPASEs constitute a comprehensive biomarker for predicting prognosis and monitoring the TIME in LUAD patients. Specifically, CDKN2A stands out as a potential prognostic biomarker and drug target for LUAD.